2012
DOI: 10.3389/fgene.2011.00113
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Quantification of cis- and trans-Regulated Genes Responding to Marek’s Disease Virus Infection via Analysis of Allele-Specific Expression

Abstract: Marek’s disease (MD) is a commercially important neoplastic disease of chickens caused by Marek’s disease virus (MDV), a naturally occurring oncogenic alphaherpesvirus. Selecting for increased genetic resistance to MD is a control strategy that can augment vaccinal control measures. To identify high-confidence candidate MD resistance genes, we conducted a genome-wide screen for allele-specific expression (ASE) amongst F1 progeny of two inbred chicken lines that differ substantially in MD resistance. High throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…Our group has previously demonstrated that Jak-STAT is an important cellular pathway involved in genetic basis of MD resistance [20,30]. Similarly, we also noted that genes in Jak-STAT pathway are transcriptionally up-regulated in susceptible line 7 and not in the resistant line 6.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Our group has previously demonstrated that Jak-STAT is an important cellular pathway involved in genetic basis of MD resistance [20,30]. Similarly, we also noted that genes in Jak-STAT pathway are transcriptionally up-regulated in susceptible line 7 and not in the resistant line 6.…”
Section: Discussionsupporting
confidence: 69%
“…However, it is worth noting transcript profiling using spleens and other organs suffers from the potential confounding influence of differences in cellular composition and reagents to properly quantify each cell subtype are limiting in chicken. Thus, the high degree of overlap between our current results, which utilized cultured cells from defined chicken lines, and those from our other studies that used actual birds [11,12,20,30] for the identification of critical pathways suggests that CEF are reasonable models. This agreement also suggests an important contribution of innate immunity towards MD genetic resistance.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Host genetic resistance is considered as an attractive approach to augment the current control measure against MD [4,[13][14][15]. Host genetic resistance to MD was first noticed in the 1940s [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The second goal was to demonstrate the power and utility of using ASE to identify specific genes impacting disease and genetic resistance. Previously, we identified 4528 SNPs in 3718 genes that exhibit ASE in response to MDV infection using F 1 progeny from experimental inbred White Leghorn layer lines that differ greatly in MD genetic resistance [ 13 , 14 ]; lines 6 and 7 are MD resistant and susceptible, respectively. Here we show that these genes with cis-regulatory elements account for the majority of the genetic variation between these two experimental White Leghorn (egg laying) lines and verify our genomic predictions by creating lines differentiated for the identified cis-regulatory elements that demonstrate associated changes in MD resistance.…”
Section: Introductionmentioning
confidence: 99%